A Systematic Review of the Psychometric Properties of Multidimensional Trait Perfectionism Self-Report Measures. Issue 2 (June 2020) - Lo, Alice; Hunt, Caroline; Abbott, Maree J.
Abstract: Different and evolving conceptualisations of perfectionism have led to the development of numerous perfectionism measures in an attempt to capture the true representations of the construct. It is, therefore, important to ensure that these instruments are valid and reliable. The present systematic review examined the literature for the psychometric properties of the most commonly used general multidimensional trait perfectionism self-report measures. Relevant studies were identified by a systematic electronic search of academic databases. A total of 349 studies were identified, with 38 of these meeting inclusion criteria. The psychometric properties presented in each of these studies were subjected to assessment using a standardised protocol. All studies were evaluated by two reviewers independently. Results indicated that while none of the included measures demonstrated adequacy across all of the nine psychometric properties assessed, most were found to possess adequate internal consistency and construct validity. The absence of evidence to support adequate measurement properties over a number of domains for the measures included in this review may be attributed to the criteria of adequacy used, with some appearing overly strict and less relevant to perfectionism measures. Clinical and research relevance of the present findings and directions for future research are discussed.